Antituberculosis activity of hydrazones derived from 4-fluorobenzoic acid hydrazide - KAYMAKÇIOĞLU, BEDİA (SPRINGER BIRKHAUSER, 2009)
A series of substitututed methylene/ethylene 4-fluorophenylhydrazide derivatives (3a-p) was synthesized with the aim of evaluating their antimycobacterial activity toward a strain of Mycobacterium tuberculosis H37Rv. Their chemical structures were confirmed by H-1-nuclear magnetic resonance (NMR) and electrospray mass spectrometry (ES-MS) spectral data, and elemental analysis. The in vitro antimycobacterial evaluation was performed according to the Tuberculosis Antimicrobial Acquisition and Coordinating Facility (TAACF) antituberculosis drug discovery program. Compound 3a, 4-fluorobenzoic acid [(2,6-dichlorophenyl) methylene]hydrazide, showed the highest inhibitory activity of all the compounds under study.
Keywords: Hydrazide-hydrazones; Antituberculosis activity; 4-fluorobenzoic acid hydrazide; ANTIMYCOBACTERIAL ACTIVITY; ANTIMICROBIAL ACTIVITY; TUBERCULOSIS; DERIVATIVES